AUTHENTIC LEADERSHIP IN THE BIBLE: A STUDY OF ITS IMPACT ON CHURCH LEADERSHIP - sugihyono, sugihyono (SEKOLAH TINGGI TEOLOGI DAN ENTREPRENEURSHIP PRINGGADING (STEP) SEMARANG, 2025)
Christian leadership in the 21st century faces the tension between managerial expectations and spiritual authenticity. Contemporary models often emphasize strategic planning, institutional hierarchy, and charismatic influence. In contrast, biblical leadership is portrayed as emerging through divine calling, spiritual formation, and character refinement. This paper explores the concept of authentic leadership through the lens of biblical narratives using a qualitative, descriptive-theological approach. By analyzing the lives of Joseph, Moses, Joshua, Saul, David, Solomon, and Jesus Christ, the study highlights how authentic leadership in the Bible is consistently associated with suffering, humility, obedience, and divine appointment. The analysis integrates contemporary authentic leadership theory with biblical theology to construct a framework of leadership grounded in spiritual integrity. The study argues that such a model is highly relevant for contemporary church leadership and proposes a renewed understanding of ecclesiastical authority rooted in servanthood, submission to God, and moral responsibility.